Bentuk Lagu Siontong Tabang Pada Ensambel Gandang Tasa Di Nagari Sunua Kurai Taji Pariaman - M. Berli Sianggian; Tulus Handra Kadir; Wimbrayardi Wimbrayardi; Uswatul Hakim (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
This research aims to describe the form of the Siontong Tabang song in the Gandang Tasa ensemble in Nagari Sunua Kurai Taji Pariaman. This study uses a descriptive qualitative method with the researcher as the main instrument, assisted by writing tools and a camera. Data were collected through literature study, observation, interviews, and documentation, with data analysis carried out through the steps of data collection, description, and conclusion drawing. The results show that Gandang Tasa is a traditional art from Pariaman, performed by an ensemble consisting of 6 to 7 players, including 6 Gandang players and 1 Tasa player. Gandang Tasa is usually performed at certain events, especially in the Tabuik ritual, to boost the spirit and solemnity of the community. The songs commonly performed in the Tabuik ritual include Oyak Tabuik, Sosoh, and Katidiang Sompong. The Siontong Tabang song plays an important role as pangka maatam in the Tabuik procession, with a short repetitive rhythmic pattern starting with Tasa playing. In the modern era, Gandang Tasa is no longer limited to traditional or ritual processes but also serves as entertainment and a means of cultural preservation for the people of Pariaman and its surroundings.